Characterizing soft-bottom epibenthic megainvertebrate communities of the Mediterranean continental shelf: a biogeographic approach - Jade Millot; Sandrine Vaz; Tarek Hattab; Christopher J. Smith; Carlos Dominguez-Carrió; Beatriz Guijarro; Grégoire Certain; Vasilis Gerovasileiou; Vincent Georges; Caterina Stamouli; Michele Casini; Chiara Manfredi; et al. (Marine Environmental Research, 2026)

Habitat shifts of the vulnerable crinoid Leptometra phalangium under climate change scenarios - Jade Millot; Vincent Georges; Valentina Lauria; Tarek Hattab; Carlos Dominguez-Carrió; Vasilis Gerovasileiou; Christopher J. Smith; Chryssi Mytilineou; M. Teresa Farriols; Marie-Claire Fabri; Pierluigi Carbonara; Daniela Massi; et al. (Progress in Oceanography, 2024)

Deficiencies in monitoring practices of marine protected areas in southern European seas - Sylvaine Giakoumi; Katie Hogg; Manfredi Di Lorenzo; Nicolas Compain; Claudia Scianna; Giacomo Milisenda; Joachim Claudet; Dimitrios Damalas; Pierluigi Carbonara; Francesco Colloca; Athanasios Evangelopoulos; Igor Isajlović; et al. (Journal of Environmental Management, 2024)

Otolith shape analysis as a tool for stock identification of two commercially important marine fishes: Helicolenus dactylopterus and Merluccius merluccius - Ana Vaz; Milene Alexandra Guerreiro; Jorge Landa; Olsen Hannipoula; Ioannis Thasitis; Giuseppe Scarcella; Laura Sabatini; Sergio Vitale; Estanis Mugerza; Kélig Mahé; Patrick Reis-Santos; Susanne E. Tanner; et al. (Estuarine, Coastal and Shelf Science, 2023)

Integrating Literature, Biodiversity Databases, and Citizen-Science to Reconstruct the Checklist of Chondrichthyans in Cyprus (Eastern Mediterranean Sea) - Ioannis Giovos; Fabrizio Serena; Dimitra Katsada; Athanasios Anastasiadis; Adi Barash; Charis Charilaou; Jason M. Hall-Spencer; Fabio Crocetta; Alexander Kaminas; Demetris Kletou; Mary Maximiadi; Vasileios Minasidis; et al. (Fishes, 2021)
Chondrichthyans are apex predators influencing the trophic web through a top-down process thus their depletion will affect the remaining biota. Notwithstanding that, research on chondrichthyans is sparse or data-limited in several biogeographic areas worldwide, including the Levantine Sea. We revise and update the knowledge of chondrichthyans in Cyprus based on a bibliographic review that gains information retrieved from peer-reviewed and grey literature, Global Biodiversity Information Facility (135 records of at least 18 species) and the Ocean Biodiversity Information System (65 records of at least14 species), and the citizen science project Mediterranean Elasmobranchs Citizen Observations (117 records per 23 species). Our updated checklist reports 60 species that account for about 70% of the Mediterranean chondrichthyan biota. The list includes 15 more species than the previous checklist and our study reports three new species for Cyprus waters, namely the blackmouth catshark Dalatias licha, the round fantail stingray Taeniurops grabatus, and the sawback angelshark Squatina aculeata. Our research highlights the need for conservation measures and more studies regarding the highly threatened blackchin guitarfish Glaucostegus cemiculus and the devil ray Mobula mobular, and stresses the importance for training a new generation of observers to strengthen the knowledge and conservation of elasmobranchs in the region.

New Mediterranean Biodiversity Records (November 2018) - MEHMET BAKİ YOKEŞ; VASILIS ANDREOU; RIGERS BAKIU; SARA BONANOMI; JUDITH CAMPS; GEORGE CHRISTIDIS; FABIO CROCETTA; IOANNIS GIOVOS; ANDREA GORI; TEA JURETIĆ; SELAHATTİN ÜNSAL KARHAN; STELIOS KATSANEVAKIS; et al. (Mediterranean Marine Science, 2018)